The sword thief [compact disc, unabridged] - Lerangis, Peter (39 clues, 2009)
When the race to find the 39 Clues leads fourteen year old Amy Cahill and her younger brother to Japan, their only chance to find the third Clue seems to lie with their unreliable uncle, Alistair Oh. Will they be foolish enough to make an alliance?